Optimization of Electrode Potential Ranges for Constructing 4.0 V Carbon‐Based Supercapacitors. Issue 3 (7th January 2020) - Ye, Meng; Guo, Hongwei; Dou, Qingyun; Guo, Hui; Hou, Ruilin; Guo, Junhong; Yan, Xingbin
Abstract: Supercapacitors (SCs) based on porous carbon exhibit high power delivery/uptake and ultra‐long cycle life but are limited by their low energy density. A critical problem is that their theoretical operating potential windows (OPWs) cannot be fully utilized, owing to the unreasonable potential ranges of electrodes, leading to significantly decreased energy density. Here, the electrode potential ranges of SCs based on activated carbon electrodes and ionic liquid electrolytes were successfully optimized by mass‐balancing and pre‐charging strategies. Consequently, the OPWs of the two resultant SCs were extended to the theoretical value of 4.0 V, and superior energy densities of 112.33 Wh kg −1 and 132.56 Wh kg −1 were obtained, respectively. Moreover, the features of these two strategies were compared. Mass‐balancing is easy to implement, but the corresponding SC shows a relatively low energy density because of the different mass loadings of two electrodes. Pre‐charging enables SC to achieve higher energy density, but it is difficult to control due to self‐discharge. Abstract : Hanging in the balance : Mass‐balancing and pre‐charging strategies are used to optimize the electrode potential ranges of supercapacitors based on hierarchically porous carbon electrodes and ionic liquid electrolyte. The mass‐balancing strategy is easy to handle, whereas the pre‐charging strategy can achieve a higher energy density. Consequently, the resultant two supercapacitors are able to operate at the theoretical voltage of 4.0 V along with superior energy densities of 112.33 Wh kg −1 and 132.56 Wh kg −1 .